The Effects of Gender-Blind Sexism on Rape Myth Acceptance: Results From a Nationally Representative Study - Stoll, Laurie Cooper (Journal of interpersonal violence, 2021)
This study uses a diverse sample that is nationally representative with regards to race and gender (N = 2,000) in an attempt to replicate and confirm Stoll, Lilley, and Pinter’s previous finding that gender-blind sexism is correlated with rape myth acceptance. As in the original study, we hypothesized that higher scores on the Gender-Blind Sexism Inventory (GBSI) would be predictive of higher scores on Stoll et al.’s Rape Myth Acceptance Scale (RMA). Gender-blind sexism builds on previous models of contemporary sexism such as hostile and benevolent sexism, modern sexism, and neosexism. It also represents an extension of racialized social system theory that explores the ways contemporary sexism operates in an era of post-racial and post-gender politics via four frames: abstract liberalism, naturalization, cultural sexism, and minimization of sexism. Unlike in the original study, however, our sample also allowed us to control for scores on the Ambivalent Sexism Inventory (ASI), the Modern Sexism Scale (MS), and the Neosexism Scale (NS) in testing this relationship. Our analysis confirmed the hypothesis that gender-blind sexism is predictive of higher rape myth acceptance among participants. Moreover, this study indicates that the GBSI offers additional value over the ASI, MS, and NS, as it was the only index of sexism tested that revealed gender-group differences within its relationship to RMA. Compared to men, women’s acceptance of rape myths was more responsive to shifts in the GBSI. We discuss the implications of our findings in terms of rape and sexual assault prevention and policy. We also provide some suggestions for how the GBSI could be used in future studies.